PERENCANAAN STRUKTUR ATAS DERMAGA GENERAL CARGO TYPE PIER BERKAPASITAS 50.000 DWT (DEAD WEIGHT TONNAGE) DERMAGA BERLIAN TANJUNG PERAK SURABYA - Sahara Aula Nanda Periwi; Nurul Rochmah (Institut Teknologi Adhi Tama Surabaya, 2023)
Tanjung Perak Port's operational region serves eastern Indonesia, making it a port capable of serving export and import container ships. Terminal. Berlian Terminal is operated by PT Berlian Terminal Services Indonesia (PT BJTI), a subsidiary of PT Pelabuhan Indonesia III (Persero). Thus far, the Berlian Terminal has been categorized as very active (Annual Report, 2018). To increase and support the active flow of commodities in the Port region, suitable infrastructure is required to avoid long wait times. The goal of this scheme is for the researcher to conduct an analysis for superstructure planning, which includes calculating pier dimensions, construction calculations, loading calculations (vertical and horizontal (ship impact force)), and design control reinforcement activities receiving/delivery to and from Berlian Terminal. So that the loading and unloading of items is more efficient, does not result in long lines, and does not result in accidents. The General Cargo pier, with a depth of 226 meters, will accommodate cargo ships with a capacity of 50,000 DWT. SPSP (Steel Pipe Sheet Pile) Grade 2 is used in the lower structure. The wharf layout is studied using SAP2000 software with 3D modeling; the results indicate that the berth dimensions are 326 m 40 m, the beam dimensions are 1000 mm 800 mm, and the plate thickness is 250 mm. SPSP with a diameter of 1016 mm is used for the piles. According to the planning results, the greatest beam moment value is 893.337 kN-m, and the largest displacement value is 0.008947 m.